PENGARUH PEMBERIAN PENGATAN VEBAL DAN NON VERBAL TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS VIII DI SMP NEGERI 24 PADANG - Mela Rosita; Yofita Sandra (Universitas Negeri Padang, 2020)
The Effect of Giving Verbal and Non-Verbal Reinforcement on the Learning Outcomes of Visual Art Student in Class VIII at SMP Negeri 24 Padang. The Purpose of This research is to describe the differences studen learning outcomes who do not use verbal and non-verbal reinforcement with the learning outcomes of students who did not use verbal and non-verbal reinforcement in class VIII SMP Negeri 24 Padang. The kind of research was quantitative approach by using quasi eksperiment method and purposive sampling as a sampling technique. In this study there was a higher average post-test result compared to the control class that did not use verbal and non verbal reinforcement, namely 85.62 in the eksperimental class and 76.78 in the control class . Based on the t-test, the results obtained tcount = 9.287 and ttable = 2.045 at the alpha level = 0.05. The researchresult obtained show that there is a difference. This study aims to implement verbal and non-verbal reinforcement in education to give appreciation for student performance in the form of rewards.Keywords: Strengthening, Verbal, Non Verbal, Learning Outcomes, Fine Art